Power control algorithms in soft aerial network - Nurul Adilah Abdul Latiff (Australia: University of Newcastle, 2014)
Soft aerial network is an alternative ways of network that can be applied in the next generation of communications world. The aim of this dissertation is to compare the soft aerial network with the terrestrial cellular system. Several advantages in the soft aerial network may overcome the drawbacks in the terrestrial cellular system. The comparison is made by the number of baseband radios needed in both soft aerial network and terrestrial cellular system.